Organizational Structure and Human Resources Management at The West Java Provincial Election Supervisory Body - Khadafi, Akbar; Nurdin, Nurliah; Pitono, Andi (GoAcademica Research & Publishing, 2024)
Bawaslu as a state auxilarry bodies, in charge of election supervision affairs must certainly have a good institutional structure from the central level to the Regency/City level, especially the target of this study, namely Bawaslu Provinsi Jawa. The purpose of this study is to analyze the management or governance of Bawaslu institutions within West Java Province and the management of Bawaslu human resources in West Java Province in improving employee performance. The method used is qualitative-descriptive. The results showed that Bawaslu of West Java Province must improve the secretariat status of each Regency/City to strengthen the institutional structure and increase the competence of human resources.